The association between killer‐cell immunoglobulin‐like receptor (KIR) and KIR ligand genotypes and the likelihood of BK virus replication after kidney transplantation. (12th September 2016) - Brochot, Etienne; Desoutter, Judith; Presne, Claire; De Araujo, Isabelle; Flahaut, Gauthier; Castelain, Sandrine; Westeel, Pierre‐François; Choukroun, Gabriel; Guillaume, Nicolas
Summary: BK virus is a common opportunistic post‐transplantation viral infection. Although some risk factors have been studied in this context, the contribution of NK cells has not been assessed in detail. In a group of kidney transplant recipients, we studied the association between (i) the likelihood of BK virus replication during the two‐year period after kidney transplantation and (ii) the genotypes of the killer cell immunoglobulin‐like receptor (KIR) repertoire and their human leukocyte antigen (HLA) ligands. Other clinical factors (such as defective organ recovery and immunosuppressive treatment) were also assessed. BK virus replication was observed in 43 of the 103 recipients (41%). Patients with BK virus replication in the plasma were more likely to display defective organ recovery in the first seven days post‐transplantation. BK virus replication was not associated with Missing KIR ligands. However, BK virus replication was more frequent in patients with responsive NK cells (i.e. when a ligand for activating KIRs was not homozygous in the recipient and present in the donor). Our results suggest that defective organ recovery and the recipient's activating KIR repertoire may be related (depending on HLA ligands present in the couple recipient / donor) to the reactivation of BK virus replication after kidney transplantation.